Montage of a Queering Deferred: Memory, Ownership, and Archival Silencing in the Rhetorical Biography of Langston Hughes. Issue 5 (3rd May 2016) - Summers, Ian
ABSTRACT: This article explores the intersection of archival privilege and heteronormative bias in the queering of Langston Hughes. Although it has been a common belief in LGBTQ communities that Hughes was gay, the battle over how his sexuality is defined in various biographical texts involves broader issues of dominant representations of sexuality and who gets to speak for those no longer able to speak for themselves. As such, the article examines the texts Looking for Langston and The Life of Langston Hughes as well as the discourses that surrounded both. Through this case study, it is apparent that there are still numerous cultural challenges posed to historical queering and that scholars must take an inventive approach to overcome them.